Using Administrative Data to Enhance Policymaking in Developing Countries : Tax Data and the National Accounts - Rivas, Lisbeth (IMF Working Papers; Working Paper ;, 2018)
Statistical agencies worldwide are increasingly turning to new data sources, including administrative data, to improve statistical coverage. Administrative data can significantly enhance the quality of national statistics and produce synergies with tax administration and other government agencies, supporting better decision making, policy advice, and economic performance. Compared to economic censuses and business surveys, administrative data are less burdensome to collect and produce more timely, detailed, and accurate data with better coverage. This paper specifically explores the use of value added tax and income tax records to enhance the compilation of national accounts statistics.